2015
DOI: 10.1021/acscatal.5b01594
|View full text |Cite
|
Sign up to set email alerts
|

Isostructural Molecular and Surface Mimics of the Active Sites of the Industrial WO3/SiO2 Metathesis Catalysts

Abstract: In classical, ill-defined WO 3 /SiO 2 alkene metathesis catalysts, isolated, silica-supported tungsten oxo alkylidene species are suspected to represent the catalytically active species. Here, we report the synthesis and the characterization of molecular and supported isostructural mimics of these active sites. The good activities at room temperature of these well-defined oxo alkylidene complexes indicate that the lower activity of WO 3 /SiO 2 , even after preactivation, is likely due to the difficulty to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 28 publications
2
30
0
2
Order By: Relevance
“…While o ‐alkoxybenzylidene initiating ligands have been widely used for Ru‐based catalysts (so‐called Hoveyda−Grubbs catalysts, Figure ), they are much less employed in Schrock ‐type systems. The first examples of 5‐coordinated Mo and W complexes bearing the pendant alkoxy group attached to the alkylidene ligand were synthesized in the 1990s, with only few additional reports being published since then, mostly focusing on structure rather than catalytic performance …”
Section: Introductionmentioning
confidence: 99%
“…While o ‐alkoxybenzylidene initiating ligands have been widely used for Ru‐based catalysts (so‐called Hoveyda−Grubbs catalysts, Figure ), they are much less employed in Schrock ‐type systems. The first examples of 5‐coordinated Mo and W complexes bearing the pendant alkoxy group attached to the alkylidene ligand were synthesized in the 1990s, with only few additional reports being published since then, mostly focusing on structure rather than catalytic performance …”
Section: Introductionmentioning
confidence: 99%
“…[519][520][521][522][523][524][525][526] Supporteda lkylidynes were also shownt o be active metathesis catalystp recursors. Preliminaryr eports appeared in early2 000s, [541,542] andt he applicationo fm odern characterization techniques eventually allowedf or precise controlofthe structures of thesesurface speciesand gave rise to theg enerationo fr emarkablya ctive well-defined silica-supportedMo- [543][544][545][546][547][548][549] andW-imido-alkylidenes [550][551][552][553][554][555] andmore recently W-oxo-alkylidenes [556][557][558][559][560] (Section 7.3.2.4).I nt he 1970sa nd 1980st he groups of Yermakov [561][562][563][564] andI wasawa [565,566] were thef irst to useo rganometallicp recursors (Mo(C 3 H 5 ) 4 and W(C 4 H 7 ) 4 )t op repare well-defined supported Mo and Woxides relevant to industrial systems and discriminate the activities of different oxidation states.T hese studies suggested that neither fully oxidized Mo VI /W VI nor highly reduced Mo II /W II species were responsible for the metathesis activity and that active sites likely arose from the oxidation state + IV.Recent advances in describing the redox chemistry of well-defined supported W-oxo sites in relation to alkene metathesis are discussed in Section 7.3.2.5. [441] Supportedt ungstenh ydridesr epresent as pecial classo fi nsitug enerated olefin m...…”
Section: Surface Sites In Industrial Catalystsmentioning
confidence: 99%
“…Thec orresponding well-defined oxo-alkylidene surface complex, (SiO)W(=O)(=CHtBu)-(OHMT) (Scheme 43 a), [556] is significantly more active and stable (TOF 3min 280 min À1 at 0.02 mol %; cis-4-nonene; batch). [558] DFT calculations suggest that oxo-alkylidenes are better catalysts than imido-alkylidenes because deactivation by b-H transfer from the SP metallacycle (Scheme 35) is energetically disfavored by the oxo ligand. [557] ( SiO)W( = O)( = CHtBu)(dAdPO) is more active than all the previously reported silica-supported imidoalkylidene catalysts (TOF 3min 325 min À1 ;0 .02 mol %; cis-4nonene;batch) and allows acatalyst loading as low as 50 ppm.…”
Section: Well-defined Silica-supported W-oxo-alkylidenesmentioning
confidence: 99%
“…However, it displays a low initial activity (Turnover frequency (TOF) = 12 min −1 ) in metathesis of cis oct-4-ene at 80°C. This low activity has been explained by the low thermal stability of this complex in absence of phosphine ligands [34].…”
Section: Group VI Complexes Used In Homogeneous Catalysismentioning
confidence: 99%
“…Indeed, the coordination environment of 22 More recently, Schrock et al synthesized new oxo tungsten complexes bearing various ligands and studied their grafting on silica dehydroxylated at 700°C. Ligands such as 2,6-mesitylphenoxy, 2,6-diadamantyl-methylphenoxy, thio-2,6-masitylphenoxy, or tris(tert-butoxy)siloxy were used and the corresponding carbenes were synthesized (Figure 25) [34,[89][90][91]. 2 ], is formed by protonation of the carbene moiety by the silanol group [90].…”
Section: Supported Oxo-alkyl and Oxo-carbene Tungsten Complexesmentioning
confidence: 99%